2015
DOI: 10.1177/0956797615583295
|View full text |Cite
|
Sign up to set email alerts
|

Sad as a Matter of Choice? Emotion-Regulation Goals in Depression

Abstract: Research on deficits in emotion regulation has devoted considerable attention to emotion-regulation strategies. We propose that deficits in emotion regulation may also be related to emotion-regulation goals. We tested this possibility by assessing the direction in which depressed people chose to regulate their emotions (i.e., toward happiness, toward sadness). In three studies, clinically depressed participants were more likely than nondepressed participants to use emotion-regulation strategies in a direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
191
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(212 citation statements)
references
References 34 publications
(78 reference statements)
15
191
5
1
Order By: Relevance
“…In RDoC terms, depression involves at least two major domains: increased negative affect, and decreased positive affect – corresponding to anhedonia and loss of interest as core features, and the “low PA” component of the tripartite model of depression and anxiety (Clark & Watson, 1991). Future work should explore whether emotion-regulation strategies that feed sadness levels heighten adolescent depression (e.g., Millgram, Joormann, Huppert, & Tamir, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In RDoC terms, depression involves at least two major domains: increased negative affect, and decreased positive affect – corresponding to anhedonia and loss of interest as core features, and the “low PA” component of the tripartite model of depression and anxiety (Clark & Watson, 1991). Future work should explore whether emotion-regulation strategies that feed sadness levels heighten adolescent depression (e.g., Millgram, Joormann, Huppert, & Tamir, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Impaired emotion regulation is recognized as a characteristic feature of major depressive disorder (MDD; Rive et al , 2013; Berking et al , 2014; Joormann and Vanderlind, 2014; Lei et al , 2014; Millgram et al , 2015). Depressed individuals are less likely to use adaptive emotion regulation strategies like cognitive reappraisal : a form of regulation that involves re-interpreting the meaning of a negative stimulus or event in order to improve one’s mood (Garnefski et al , 2002; Ochsner and Gross, 2005; D’Avanzato et al , 2013; Gross, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Depressed individuals may make more realistic inferences than do nondepressed people (Moore and Fresco, 2012). Moreover, Millgram, Joormann, Huppert and Tamir (2015) found that even after accounting for current sadness and happiness, people with depressive disorders chose to view sad images more frequently than did nondepressed individuals. Consequently, it is plausible that depressed people would report that their feelings should not be different, potentially reflecting the belief that it is others who should feel differently.…”
Section: Discussionmentioning
confidence: 99%